Strategi Branding Digital UMKM Pariwisata untuk Meningkatkan Daya Saing Destinasi Wisata Lokal di Jawa Tengah - Syafi'ah, Syafi'ah; Putranto, Afif Hendri; Siti Masrokhah; Wisanggeni Bagus Anggoro; Tiyan Fatkhurrokhman (DFAME Digital Financial Accounting Management Economics Journal, 2025)
This study examines the digital branding strategies implemented by tourism-based MSMEs in Central Java to enhance the competitiveness of local destinations. The study employs an exploratory approach to understand the digital communication practices carried out by business actors, focusing on the use of visual content, cultural narratives, and digital interactions as key components shaping brand identity. The findings show that MSMEs rely heavily on social media platforms to showcase destination uniqueness and build emotional engagement with potential visitors. The study identifies several major challenges, including limited technical skills, inconsistent brand identity, and weak digital reputation management, which hinder the effectiveness of branding strategies. The study emphasizes that strong branding requires improved digital competence, structured brand identity planning, and enhanced capability in handling online reviews. The study suggests that digital training, technical assistance, and multi-stakeholder collaboration are essential to strengthen the marketing foundation of local tourism destinations. Future research is encouraged to explore more specific models of branding assistance, incorporate emerging digital technologies, and involve broader tourism stakeholders in strengthening destination competitiveness.